Ruthenium-Catalyzed Direct ortho-Alkynylation of Arenes with Chelation Assistance - Ano, Yusuke; Tobisu, Mamoru; Chatani, Naoto (Synlett, 2012)
The ruthenium-catalyzed direct alkynylation of arenes with the chelation assistance of nitrogen-containing heterocycles including pyridine, pyrimidine, pyrazole, and imidazole are described. The alkynylation is successful even in the presence of an acidic N–H bond. Broad compatibility with functional groups is observed under catalytic conditions. The obtained alkynylated products could serve as precursors for polycyclic heteroarenes.
Keywords: ruthenium; alkyne; heteroarene; C–H activation; chelation